Phosphodiesterase 3A and Arterial Hypertension. Issue 2 (14th July 2020) - Ercu, Maria; Markó, Lajos; Schächterle, Carolin; Tsvetkov, Dmitry; Cui, Yingqiu; Maghsodi, Sara; Bartolomaeus, Theda U.P.; Maass, Philipp G.; Zühlke, Kerstin; Gregersen, Nerine; Hübner, Norbert; Hodge, Russell; et al.
Abstract : Background: High blood pressure is the primary risk factor for cardiovascular death worldwide. Autosomal dominant hypertension with brachydactyly clinically resembles salt-resistant essential hypertension and causes death by stroke before 50 years of age. We recently implicated the gene encoding phosphodiesterase 3A ( PDE3A ); however, in vivo modeling of the genetic defect and thus showing an involvement of mutant PDE3A is lacking. Methods: We used genetic mapping, sequencing, transgenic technology, CRISPR-Cas9 gene editing, immunoblotting, and fluorescence resonance energy transfer. We identified new patients, performed extensive animal phenotyping, and explored new signaling pathways. Results: We describe a novel mutation within a 15 base pair (bp) region of the PDE3A gene and define this segment as a mutational hotspot in hypertension with brachydactyly. The mutations cause an increase in enzyme activity. A CRISPR/Cas9-generated rat model, with a 9-bp deletion within the hotspot analogous to a human deletion, recapitulates hypertension with brachydactyly. In mice, mutant transgenic PDE3A overexpression in smooth muscle cells confirmed that mutant PDE3A causes hypertension. The mutant PDE3A enzymes display consistent changes in their phosphorylation and an increased interaction with the 14-3-3θ adaptor protein. This aberrant signaling is associated with an increase in vascular smooth muscle cell proliferation and changes in vessel morphology and function. Conclusions: The mutated PDE3A gene drives mechanisms that increase peripheral vascular resistance causing hypertension. We present 2 new animal models that will serve to elucidate the underlying mechanisms further. Our findings could facilitate the search for new antihypertensive treatments. Abstract : Supplemental Digital Content is available in the text.